Prevenção de acidentes de trabalho no Brasil sob a ótica dos incentivos econômicos - Bedin, Barbara (My University, 2014)
The health is a part of the government´s permanent concerns agenda and also of non-governmental entities at the entire world. The worker´s health as collective interest subject is inserted inside of this context. In Brazil, where the occupational diseases and accidents is significant, it accounts itself demanded more and more attention from the competent authorities to promote public politics that they strengthen the prevention and the security in the environment of the labor. This work has as objective to identify the Economic Theory´s incentives system and apply them in the Labor Law as instrument of help in the prevention or reduction of the labor misfortunes, through the Economic Analysis of the Law. To observe the Law not only as a coercion system, but also as a incentives system with implicit prices it allows that the individuals´ choices are directed to the proposed objectives by the legislation.
A saúde faz parte da agenda de preocupações permanentes do governo e também de entidades não-governamentais de todo o mundo. A saúde do trabalhador, como assunto de interesse coletivo, está inserida dentro desse contexto. No Brasil, onde o índice de acidentes e doenças ocupacionais é significativo, tem-se exigido cada vez mais atenção das autoridades competentes para promover políticas públicas, que reforçem a prevenção e a segurança no meio ambiente do trabalho. Este trabalho tem como objetivo identificar o sistema de incentivos, da Teoria Econômica e aplicá-los no Direito do Trabalho como instrumento de auxilio na prevenção ou diminuição dos infortúnios laborais, através da Análise Econômica do Direito. Observar o Direito não só como um sistema de coerção, mas também como um sistema de incentivos com preços implícitos permite que se direcionem as escolhas dos indivíduos aos objetivos propostos pela legislação.
Keywords: Direito; Acidentes do trabalho; Análise econômica do direito; Incentivos econômicos; Meio ambiente do trabalho; Prevenção; Direito do trabalho; Industrial accidents; Economic analysis of the law; Economic incentives; Environment of the labor; Prevention; Labor law